Optimization and Characterization of Self Nano Emulsifying Drug Delivery System (SNEDDS) of Curcumin with D-Optimal Mixture Design Method - Kusumawati, Mulyaningtyas Ayu; Iswandi, Iswandi; Kuncahyo, Ilham (East Asian Journal of Multidisciplinary Research, 2024)
Curcumin, known for its anti-inflammatory, antibacterial, anticarcinogenic, and antioxidant properties, faces challenges due to poor water solubility and low bioavailability as a BCS class II compound. The study investigates using a self-nanoemulsifying drug delivery system (SNEDDS) to enhance these properties, optimizing the formulation with the D-Optimal Mixture Design method. Sixteen formulas were prepared using oleic acid, Tween 80, and PEG 400. Each formula was characterized by particle size, % transmittance, emulsification time, and drug loading. The optimized formula, containing 10% oleic acid, 70% Tween 80, and 20% PEG 400, achieved a particle size of 80.167 nm, an emulsification time of 39.36 seconds, near 100% transmittance, and high drug loading.